2023
DOI: 10.13164/re.2023.0063
|View full text |Cite
|
Sign up to set email alerts
|

SAMPLE Dataset Objects Classification Using Deep Learning Algorithms

Abstract: The main topic of the article is automatic target classification of the synthetic aperture radar images based on the dataset composed of measured and synthetic data. The original contribution of the authors is their own topology of the convolutional neural network (CNN) with 1, 2, 3, and 4 tiers. The original convolutional neural network is used to classify radar images from the Synthetic And Measured Paired and Labeled Experiment (SAMPLE) dataset which consists of SAR imagery from publicly available datasets … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…The DL-based technique handles an enormous amount of data urged a need for automation in 5G and beyond cellular networks. The DL models, such as Convolution Neural Network (CNN) [14], Multi-Layer Perceptron (MLP) [15], Long Short Term Memory (LSTM) Network [16], Residual Network (ResNet) [17], Recurrent Neural Network (RNN), Convolutional and Long Short-Term Memory Deep Neural Network (CLDNN) [18], and ResNet+LSTM [19] have been developed to improve the AMC algorithms. In [20], the authors have compared the different types of input data formats for the modulation classification process and concluded that the I/Q format gives the best classification accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…The DL-based technique handles an enormous amount of data urged a need for automation in 5G and beyond cellular networks. The DL models, such as Convolution Neural Network (CNN) [14], Multi-Layer Perceptron (MLP) [15], Long Short Term Memory (LSTM) Network [16], Residual Network (ResNet) [17], Recurrent Neural Network (RNN), Convolutional and Long Short-Term Memory Deep Neural Network (CLDNN) [18], and ResNet+LSTM [19] have been developed to improve the AMC algorithms. In [20], the authors have compared the different types of input data formats for the modulation classification process and concluded that the I/Q format gives the best classification accuracy.…”
Section: Introductionmentioning
confidence: 99%